LIME (Citrus aurantifolia S.) SOAP AS AN ALTERNATIVE TO HALAL PRODUCTS - Eva Nauli Taib; Nabila Salsabila; Annisa Putri; Della Maulidayanti (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2023)
The Aceh Ulema Council (MUI) issued MUI fatwa Number 83 of 2023 regarding forms of support for the Palestinian struggle, namely prohibiting buying products that are clearly affiliated with supporting Israeli aggression. One way is not to use Zionist products, we can avoid this by replacing dish soap with natural ingredients. The aim of this research is to utilize lime plants (Citrus aurantifolia .S) as well as alternative halal products as dish washing soap and test the effectiveness of washing soap for removing dirt. The method in this research is experimental. The tools used are containers, wooden stirrers, and napkins. The ingredients used are distilled water, lime extract (Citrus aurantifolia .S), and a soap formula which is sold in packages. Presentation of data in the form of images and tables. The research results show that soap from lime extract (Citrus aurantifolia .S) is proven to be able to remove fat dirt and can create a fragrance resulting from the addition of fragrance in the manufacturing process. The conclusion of this research is that making dishwashing soap from lime extract can remove dirt, smell good and can be an alternative to halal products.